"Asthma phenotypes: the intriguing selective intervention with Montelukast". Issue 1 (December 2016) - Marcello, Cottini; Carlo, Lombardi
Abstract Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation and a variable course associated with various underlying mechanisms that can differ between individuals. Patients with asthma can therefore exhibit different phenotypes, a term used to define the observable characteristics of an organism resulting from the interaction between its genetic makeup and the environment. The heterogeneity of asthma has received a large amount of attention in the last few years in order to better tailor treatment according to the different clinical and biological phenotypes of the disease. Specific asthma phenotypes may require an approach to treatment sometimes different from that recommended by current guidelines, so a personalized approach to asthma pharmacotherapy is recommended. Growing evidence suggests that leukotrienes play an important role in the pathogenesis of bronchial asthma. The mechanisms of action of leukotriene-receptor antagonists theoretically predict a good response in some asthma "phenotypes".In this article we have performed an analysis of the recent literature (controlled clinical trials and real-life studies) about a possible selective intervention with Montelukast in specific asthma phenotypes.